A stable countryside for a stable country? The effects of a DCFTA with the EU on Tunisian agriculture - Bettina Rudloff (Stiftung Wissenschaft und Politik (SWP), 2020)
Agriculture is central to the stability of Tunisia's economy and society. The new Deep and Comprehensive Free Trade Agreement (DCFTA) under negotiation with the EU offers opportunities for the agricultural sector, but also presents risks for the country as a whole. Within Tunisia there is strong emotional resistance to the DCFTA. Its intensity is comparable to the strength of feeling against the Transatlantic Trade and Investment Partnership (TTIP) in Germany a few years ago. In addition to criticisms of specific topics in the talks, a string of issues fuel this categorical rejection: wariness of European dominance; negative experiences with transformations in the agricultural sector, especially in relation to land ownership; as well as the tradition - prevalent across North Africa - of securing food security through protectionist trade policy. Sustainability impact assessments demonstrate positive welfare effects on growth and standard of living - but many concerns about ecological and social repercussions appear justified. Such negative effects can be avoided through concrete solutions within the agreement, and even better through appropriate Tunisian policies. The EU can address the categorical rejection by almost all stakeholders in Tunisia through better communication during negotiations. As well as appealing for commitment and responsibility on the Tunisian side, it will be important to approach Tunisian sensitivities with awareness and respect. Above all, Tunisian researchers should be more involved in DCFTA sustainability impact assessments and participate in public debate on these studies. Regardless of the success or failure of the talks, Tunisian agriculture needs to be promoted and developed. The organic sector offers great export opportunities and attractive employment opportunities for young people.
Keywords: 320; Marktzugang; Zölle; Assoziierungsabkommen